Cross-border movement and women's health: how to capture the data - Merry Lisa; Gagnon Anita J; Hemlin Isabelle; Clarke Heather; Hickey Jason (BMC, 2011)
Abstract Introduction The movement of women across international borders is occurring at greater rates than ever before, yet the relationship between migration and women's health has been under-explored. One reason may be difficulty measuring migration variables including country of birth, length of time in country, immigration status, language ability, and ethnicity. A range of social, environmental, cultural, and medical characteristics associated with the pre-, during- and post-migration phases are also important to consider. The objective of this paper is to present challenges and solutions in measuring migration and related variables via survey-like questionnaires administered to international migrant women. Methods The development, validation, and translation of two questionnaires subsequently applied in studies of migrant women during pregnancy, birth and postpartum were used as case examples to highlight related measurement issues. Results Challenges: (1) Measuring socio-cultural, medical and environmental variables across the pre-during-post migration phases (since questions must be framed so that data relating to each phase of migration are captured); (2) Obtaining data for complex patterns of migration (i.e., multiple movements between multiple destinations); and (3) answering long questions across a time continuum. Solutions: (1) Using interviewer-assisted rather than self-administered questions; (2) Adding probes and explanations to 'walk' participants through their migration experiences; (3) Identifying variables (e.g., trafficking) better captured using non-questionnaire data collection methods or better not collected (e.g., ethnicity) due to extreme variations in meaning. Conclusion Carefully constructed and translated survey questionnaires are practical tools for the collection of a breadth of migrant data. These data, including detailed accounts of countries lived in, length of time in those countries, immigration status, change in status, language fluency, and health insurance eligibility offer rich descriptions of the population under study and make research findings with regards to migration more interpretable. Analyses by a range of migration indicators are facilitated through survey-like questionnaire data of this type.